The Influence of Health Worker Services on Patient Satisfaction with Islamic Spiritual Concepts as a Moderating Variable - Afip Sultoni; Slamet Santoso; Riawan Riawan; Sri Hartono (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Quality healthcare services not only emphasize technical medical aspects but also consider empathy and patients’ spiritual values. In Indonesia, where the majority of the population is Muslim, Islamic-based healthcare services play an important role in shaping patient satisfaction. This study aims to analyze the effects of healthcare staff services, service quality, and healthcare staff empathy on patient satisfaction, with Islamic service as a moderating variable. This study employed a quantitative approach with a cross-sectional design involving 100 outpatient respondents. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that healthcare staff services, service quality, and healthcare staff empathy have positive and significant effects on patient satisfaction. Furthermore, Islamic service was found to strengthen the relationships between these variables and patient satisfaction. The discussion highlights that integrating Islamic values into healthcare services enhances patients’ holistic service experiences. This study concludes that professional, empathetic, and spiritually grounded healthcare services play a crucial role in improving patient satisfaction.